Adapting Fiscal Decentralization Design to Combat Climate Change - Martinez-Vazquez, Jorge (World Bank, Washington, DC, 2021)
There are still many countries around the world that have not effectively engaged their subnational governments in their climate change strategies and policy frameworks. Where subnational levels are involved, generally they still play a relatively small role. This paper examines how the principles of fiscal decentralization design (in expenditure and revenue assignments, transfers, and borrowing) can be adapted to successfully engage subnational governments in fighting climate change. In addition, the paper critically reviews ongoing international practices, both effective and less effective, that involve subnational governments in climate change mitigation and adaptation. Shared responsibility for policy and program design and implementation, fee-or charge-funded adaptation activities, objective-targeted intergovernmental transfers, and the use of green bonds are some of the most promising approaches analyzed. Clearly, there is ample space ahead for the further involvement of subnational governments across the world in combating climate change.